The red boat - Cumming, Hannah. frey50 (Swindon : Child's Play, 2012)
Posy feels lonely in her new house. She doesn't know anyone, and worries about making friends. One day, while exploring the garden, she come across a red boat. Posy and her dog George have lots of fun in the red boat. They decide to visit it one night when they can't sleep, and that's when something magical happens.
Keywords: Moving, Household; Human-animal relationships; Boats and boating; Gardens; Moving, Household; Children's stories